Рискоориентированный подход к системе показателей оценки деятельности страховой организации (Путеводитель предпринимателя)
This article investigates issues related to the systematization of indicators to assess the financial condition and financial stability of the insurance organization, the comparative analysis of the effectiveness of performance in terms of an adequate assessment of the insurer, justified the need to supplement the traditional system of indicators such groups as indicators for assessing the investment, financial risk assessment.